Pengaruh Workplace Spirituality Terhadap Kinerja Karyawan - Raja Al-Faris Luthfi; Rusman Frendika (Bandung Conference Series: Business and Management, 2023)
Abstract Workplace spirituality is a concept that discusses the relationship between spiritual aspects and the work environment. Spirituality at work is not about bringing religion into the realm of work, but rather the ability of employees as spiritual beings to bring their whole self to work. Based on the phenomena that the researcher summarizes, the problems in this study are formulated as follows: (1) How is the Workplace Spirituality in the Jalancagak SMAIT unit As-syifa Al-Khoeriyyah Foundation, Subang, West Java. (2) How is the performance of the Jalancagak SMIT Unit As-Syifa Al-Khoeriyyah Foundation, Subang, West Java. (3) How big is the influence of workplace spirituality on employee performance at the Jalancagak SMAIT As-siyfa Al-Khoeriyyah Foundation, Subang, West Java. Researchers used a descriptive verification method with a quantitative approach. The population selected in this study were 51 teachers at SMAIT AS-SYIFA BOARDING SCHOOL Subang. With the sampling technique using saturated sampling or commonly called the census technique, which is one of the non-probability techniques, the total sampling is 51 respondents, which means it is counted as a whole. Data collection techniques used in this study were questionnaires, interviews, observation, and literature study. Abstrak. Workplace spirituality adalah sebuah konsep yang membahas tentang kaitan aspek-aspek spiritualitas dengan lingkungan kerja. Spiritualitas dalam pekerjaan bukan tentang membawa agama ke dalam ranah pekerjaan, melainkan kemampuan karyawan sebagai makhluk srpiritual untuk menghadirkan keseluruhan dirinya untuk bekerja. Beradasarkan fenomena yang peneliti rangkum, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Bagaimana Workplace Spriritulity Pada unit SMAIT Jalancagak Yayasan As-syifa Al-Khoeriyyah Subang Jawa Barat. (2) Bagaimana Kinerja Pada unit SMIT Jalancagak Yayasan As-syifa Al-Khoeriyyah Subang Jawa Barat. (3) Seberapa Besar Pengaruh Workplace Spirituality Terhadap Kinerja Karyawan Pada unit SMAIT Jalancagak Yayasan As-siyfa Al-Khoeriyyah Subang Jawa Barat. Peneliti menggunakan metode deskriptif verifikatif dengan pendekatan kuantitatif. Populasi yang dipilih dalam penelitian ini adalah guru SMAIT AS-SYIFA BOARDING SCHOOL Subang yang berjumlah 51 guru. Dengan teknik pengambilan sampel menggunakan sampling jenuh atau biasa disebut teknik sensus yang merupakan salah satu dari teknik non-probability total sempling berjumlah 51 responden yang berarti dihitung secara keseluruhan. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah kuesioner, wawancara, observasi, dan studi pustaka.